2020
DOI: 10.36103/ijas.v51i5.1150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluting the Ability of Pleurotus Ostreatus Aqueous Extract to Modulate Genotoxicity Induced by Cyclophosphamide in Mice Bone Marrow Cells

Abstract: This study was aimed to evaluate the ability of local oyster mushroom(Pleurotus ostreatus; ID: MF065715.1; cultivated until maturation in growth medium containing cumin extract) to modulate the genotoxicity induced by cyclophosphamide (CP) in bone marrow cells of mice. In vivo genotoxicity was assessed by quantifying the incidence of micronucleated polychromatic erythrocytes in the bone marrow cells of mice that were administered different doses of P.ostreatus extract (150, 200,250, and 300 mg/kg/day( respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nine treatments were tested using different types of media. Results shown in Table (2), treatment T8 recorded the highest daily growth rate for shiitake strain, which amounted to 1.8 cm/day, followed by treatments (T7, T3) with a growth rate of (1.5 cm/day), then treatments (T1, T2 and T4) with a growth rate (1.4 cm/day), and treatment T6 with a growth rate, while treatments (T9, T5) recorded the lowest growth rate compared to the rest of the treatments, reaching (1.1 cm/day) (picture 1). This result is consistent with that reported by [13], who reported growth values ranging from 0.76 -1.12 cm per day (1.3 cm/day).…”
Section: Daily Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Nine treatments were tested using different types of media. Results shown in Table (2), treatment T8 recorded the highest daily growth rate for shiitake strain, which amounted to 1.8 cm/day, followed by treatments (T7, T3) with a growth rate of (1.5 cm/day), then treatments (T1, T2 and T4) with a growth rate (1.4 cm/day), and treatment T6 with a growth rate, while treatments (T9, T5) recorded the lowest growth rate compared to the rest of the treatments, reaching (1.1 cm/day) (picture 1). This result is consistent with that reported by [13], who reported growth values ranging from 0.76 -1.12 cm per day (1.3 cm/day).…”
Section: Daily Growth Ratementioning
confidence: 99%
“…Lentinula edodes is widely cultivated all over the world and is considered a traditional delicacy in Southeast Asia due to its high nutritional value, unique flavour, attractive taste and aroma. Mushrooms are considered a complete healthy food suitable for all age groups, from children to the elderly because they are rich in proteins, dietary fibres, vitamins and minerals [1][2][3][4]. Edible mushrooms are collected from their natural environment and have been consumed by humans throughout history.…”
Section: Introductionmentioning
confidence: 99%
“…People are increasingly looking for a healthy lifestyle and therefore healthy foods, which can also provide innovative treatment options. To this end, public awareness of the need for a careful and healthy diet has increased [2,3]. There is a growing demand for healthy foods and food products related to their nutritional function, which have health benefits, namely functional foods, as well as nutritional supplements and/or nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Necessary for the human body, B vitamins are nominated to occupy a treatment of immunodeficiency disease hypertension. It was found that it contributes to treating depression and mental illness (Farhan et al, 2018;Farhan and Chechan, 2020;Farhan et al, 2020;Hadwan et al, 2021). The genus Pleurotus ranks second in terms of production at the global level after the white agricultural fungus, Agricus bisporus (Adjapong et al, 2015;Chechan et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%